Adrenergic receptors gene polymorphisms and autonomic nervous control of heart and vascular tone - Matušková, L; Javorka, M (Physiological research, 2021)
Adrenergic receptors (ARs) are the primary targets of catecholamines released from the sympathetic nerve endings during their activation. ARs play a central role in autonomic nervous system and serve as important targets of widely used drugs. Several ARs gene polymorphisms were found to be associated with cardiovascular disease in previous clinical studies. Although more precise mechanism of the polymorphisms influence on autonomic control of cardiovascular system was studied in many previous physiological studies, their results are not unequivocal. This paper reviews the results of clinical and physiological studies focused on the impact of selected common single nucleotide polymorphisms of ARs genes involved in sympathetic control on cardiovascular system and its control. In summary, many studies assessed only a very limited range of cardiovascular control related parameters providing only very limited view on the complex cardiovascular control. The overview of partially contradicting results underlines a need to examine wider range of cardiovascular measures including their reactivity under various stress conditions requiring further study. It is expected that an effect of one given polymorphism is not very prominent, but it is suggested that even subtle differences in cardiovascular control could - on a longer time scale - lead to the development of severe pathological consequences.
Keywords: autonomní nervový systém; Heart; jednonukleotidový polymorfismus; Polymorphism, Single Nucleotide; Cardiovascular System; kardiovaskulární systém; Autonomic Nervous System; Receptors, Adrenergic; sympatický nervový systém; Sympathetic Nervous System; adrenergní receptory; srdce